Studi Mula Pembuatan Purwa-rupa Smartphone Document Scanner Stand Dengan Metode Taguchi - Rahman Hakim; Agung Nirwana; Annisa Fyona; Widodo Widodo; Benny Haddli Irawan (Jurnal Teknologi dan Riset Terapan (JATRA), 2021)
The need for digitally scanned documents has become a public need these days. Furthermore, smartphone usage with supporting applications to scan barcodes and documents digitally has become a trend. The problem that often occurs when scanning documents is the instability of the hand-held document. In addition, the 3-axis coordinate determination of a smartphone is also not easy to control. Therefore, tools are needed to speed up and simplify the scanning process. This research aims to create a tool that can increase work productivity when scanning documents using a smartphone. Market analysis, engineering planning, and prototypes have been carried out to learn what will decide mass production and sale in general. The data analysis method used a full factorial design, using gender as a factor and preparation time and data scanning time as levels. The initial preparation time to retrieve photo and PDF documents from the initial preparation and scanning results on average takes 4.357 minutes with Std. Deviation 1.739 minutes. As for the following scan with the same paper size, it only takes 1.242 minutes with Std. Deviation 0.201 minutes. The production cost of this prototype is 126.22USD with Std.Deviation 11.36USD. Even though the production cost is the highest, it has a TKDN value of 100% and the application of PBL by students who can carry it out well.